A Novel Signature of Serum Interleukin 3 in Ankylosing Spondylitis - Abd Ali, Baneen Mueen; Sharquie, Inas K.; Gorial, Faiq I. (Iraqi Journal of Science, 2026)
spondylitis (AS), which is regulated by numerous cytokines. Interleukin-3 (IL-3) involvement as a biomarker for AS has remained unexplored. Therefore, this study aims to assess serum IL-3 levels to improve the accuracy of AS diagnostics and enhance targeted therapies while exploring the role of human leukocyte antigen (HLA-B27) in influencing IL-3. The study examined the IL-3 serum levels of 88 patients with AS and 44 healthy controls recruited from the Baghdad Teaching Hospital. Patients with AS disease were further divided into two subcategories according to AS status: inactive (n = 44) and active (n = 44). Serum IL-3 titers were quantified using enzyme-linked immunosorbent assay (ELISA). Clinical parameters like complete medical histories, body mass index, sex, age, and disease duration were also recorded. Additionally, laboratory disease parameters, such as HLA-B27, C-reactive protein, and rheumatoid factor, were analyzed. IL-3 levels were higher in the AS patients (456.63 ± 237.118 pg/ml) than in the healthy controls (178.21 ± 16.015 pg/ml, p < 0.01). The mean IL-3 levels were highest in patients with active AS (663.27 ± 156.293 pg/ml) and became incrementally lower with reduced disease severity, inactive, 250 ± 44.148 pg/ml. Serum IL-3 exhibited strong diagnostic for AS, demonstrating a cut-off value of ≥ 193 pg/ml as well as an area under the curve score of 0.997. Sensitivity, accuracy, in addition to specificity were 98.9%, 91.67%, and 77.3%, respectively. In conclusion, serum IL-3 levels were significantly elevated in AS patients and correlated to the disease's activity. This suggests that IL-3 could be valuable in predicting disease severity and monitoring AS progression.